MELURUSKAN PENAFSIRAN TENTANG PANCASILA - Hajri, Wira Atma; Idris, Zulherman; Riantono, Masriko (UIR PRESS, 2019)
Pancasila has a very strategic position in the life of the nation and state. Pancasila is not only as a source of all sources of law, but also as the basis of the state, state ideology, and philosophical basis of the state. Nevertheless, ironically the interpretation of Pancasila itself is even diverse. It simply depends on the holder of power. The purpose of this study is to find out the correct interpretation of Pancasila in Indonesia, especially the principle of the Almighty God who illuminates the other precepts. This research is a library research. Analysis was carried out qualitatively using a statutory approach, case approach, conceptual approach, and historical approach, political approach, and comparison approach. The results of this study are that there is a deviation from Pancasila when Pancasila is not interpreted correctly and does not want to be honest with the history of the formulation of Pancasila itself. Therefore it is not surprising when in practice, there are laws, understandings, actions or actions that are contrary to Pancasila.